1984
DOI: 10.1177/073724778400900303
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the WISC-R V-P Discrepancy at Learning Disabled Children's Triannual Reevaluation

Abstract: stability of WISC-R Verbal-Perforal reevaluation of 71 learnresults revealed a slight nce, with a correlation acerpancy scores.atation of the V-P ample was obre best to beracterInasmuch as the Wechsler Intelligence Scale for Children-Revised (WISC-R) (Wechsler, 1974) is the psychodiagnostic test most frequently used by school psychologists, it is surprising to find how little information is available about its stability over time. This issue is even more critical to the current practice of school psychology be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Having associated chronic diseases, congenital abnormalities, comorbid psychiatric diagnosis, or being refugees were exclusion criteria. SLD diagnosis was made through a combination of psychiatric interviews evaluating reading, writing, and mathematics skills of the children, Teachers and Parents Information Form and the Specific Learning Difficulty Battery by a child and adolescent psychiatrists [ 20 ]. Children having IQ scores below 70 on Wechsler Intelligence Scale for Children-revised form and comorbid psychiatric diagnosis were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Having associated chronic diseases, congenital abnormalities, comorbid psychiatric diagnosis, or being refugees were exclusion criteria. SLD diagnosis was made through a combination of psychiatric interviews evaluating reading, writing, and mathematics skills of the children, Teachers and Parents Information Form and the Specific Learning Difficulty Battery by a child and adolescent psychiatrists [ 20 ]. Children having IQ scores below 70 on Wechsler Intelligence Scale for Children-revised form and comorbid psychiatric diagnosis were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Such injections are associated with an immediate and substantial rise in blood pressure that is reversed by L-arginine [26], indicating that the continuous release of nitric oxide from endothelial cells helps to maintain the vasculature in a dilated state. A vasculo-protective effect for EDRF is suggested by EDRF inhibition of platelet activation and smooth muscle cells migration and proliferation [27]. An EDRF related mechanism in SSc is suggested by the reported decrease in endothelial-dependent vasodilatation responses to substance P in SSc [28].…”
Section: Endothelial Dependent Relaxation Factor-nitric Oxide (Edrfno)mentioning
confidence: 99%
“…Bannatyne developed an alternative classification in which the subtests are clustered into four categories. These categories are currently among the most widely used scoring units for diagnosing children with SLD (22,29,30,31). However, in another study (26), it was found that the scores obtained from the subtest categories of WISC-R were not conclusive.…”
mentioning
confidence: 97%